A study of the availability and utilisation of library electronic resources by undergraduate students in private Universities in Ogun state, Nigeria (2014)
The degree of availability and utilization of e-resources in any university library may influence the information services provision to students. The main objective of the study was to investigate the availability and utilization of e-resources by undergraduate in selected private university libraries in Ogun State, Nigeria. Descriptive survey design was adopted and study population consisted of 9700 undergraduates from Babcock and Redeemer’s universities. Simple random was used to select a sample of 291 and the questionnaire was the main instrument used for data collection. Data were analyzed using SPSS specifically descriptive statistics consisting of tables of frequency and percentage. The findings revealed that the internet was readily available in Babcock (83.5%) and Redeemer (92.8%), while other e-resources were not readily available. Most of the respondents in Babcock (64.0%) and Redeemer (89.1%) used the e-resources for assignment and research/project. Poor internet connectivity, lack of relevant e-resources in various disciplines, erratic power supply, and lack of technical know-how were the major challenges faced by the respondents. The internet and e-journals are important sources of information for both universities undergraduate students. Also, the availability and use of e-resources has no doubt contributed meaningfully to the information acquisition for class work, assignment and research needs of the students.